Implementasi POAC dalam Manajemen Pendidikan Modern - Muhamad Faiz; Rafli Suciamy; Siti Zaskia; Hesti Kusumaningrum (Reflection : Islamic Education Journal, 2024)
POAC (Planning, Organizing, Actuating, Controlling) is a management framework used to improve effectiveness in various sectors, including education. In modern education management, the implementation of POAC plays a crucial role in achieving the goals of efficient and quality education. Planning helps set the long-term vision and strategy of the educational institution. Organizing ensures that human and material resources are managed effectively. Actuating involves leadership and motivation to ensure that all parties are active in the educational process. Control is carried out through periodic evaluation and monitoring to ensure the achievement of goals. Research shows that the proper implementation of POAC can improve learning quality, operational efficiency, and student satisfaction. The application of POAC in modern education management is an important strategy in creating educational institutions